SERVIÇOS ECOSSISTÊMICOS DA PAISAGEM FLUVIAL - Aminy Kokehara (2024)
This dissertation investigates ecosystem services in urban water landscapes, focusing on riparian woodlands and their relevance to biodiversity, environmental quality, and human well-being, using the city of Campo Grande, MS, as the study application. The dissertation is structured into three chapters. The first chapter analyzes the green cover in the riparian zones of urban watercourses using the Normalized Difference Vegetation Index (NDVI). It was found that there is a predominance of areas without vegetation and an association between the absence of vegetation and the channeling of watercourses, especially in the city center. The second chapter addresses the effects of accelerated urbanization, highlighting soil impermeabilization and the resulting chronic flooding. It concludes with the proposal of a landscape-based approach to urban water management, emphasizing the conservation of riparian woodlands in the micro-basins of the Anhanduí and Segredo streams. The third chapter focuses on the ecosystem services provided by riparian woodlands, correlating the ecological integrity of these areas with water quality and vegetation cover. The conclusion is that maintaining the ecological integrity of riparian areas is essential for the provision of ecosystem services, recommending conservation policies and sustainable urban planning to improve the quality of life in Campo Grande.